Gerakan Pramuka Penegak Membangun Karakter Dan Kontribusi Sosial Masa Depan - Erlina Munthe (Jurnal Pelita Pengabdian Masyarakat, 2024)
The Rover Scout Movement is an important part of the Scout Movement that aims to build strong character and inspire youth to contribute to society. Keywords: Rover Scout Movement, character, social contribution. The Rover Scout Movement is a stage in the journey of a scout who has reached adolescence. Through diverse activities, the Rover Scouts aim to develop their character and instill noble values such as leadership, honesty, independence, cooperation, and a sense of responsibility. In this regard, the Rover Scouts have an important role in preparing the younger generation to become active, responsible, and socially concerned citizens. In addition to focusing on character development, the Rover Scout Movement also encourages its members to make significant social contributions. Through community service activities, the Rover Scouts engage in various projects and programs aimed at advancing society, such as environmental activities, fundraising for charity, or providing assistance to those in need. By participating in these endeavors, the Boy Scouts learn about the values of caring, empathy, and self-sacrifice. The Rover Scout Movement is not just another youth organization, but also a place to hone individual potential and play an active role in shaping a better future. By developing strong character and making social contributions, the Boy Scouts encourage youth to become agents of change who play a role in building a better, fairer, and more sustainable society